2015
DOI: 10.1080/19393210.2014.993430
|View full text |Cite
|
Sign up to set email alerts
|

Lead, cadmium, arsenic and mercury in canned tuna fish marketed in Tehran, Iran

Abstract: Fifty-four canned tuna fish samples corresponding to 10 widely used different brands were purchased from local markets in Tehran, Iran during 2012-2013 and analysed on heavy metals. Mercury was determined by a direct mercury analyser without any sample preparation. For analysis of other elements samples were digested using a microwave apparatus. Lead and cadmium were determined by graphite furnace atomic absorption spectrometry and arsenic via hydride vapour generation. All samples had arsenic and mercury cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 33 publications
(40 reference statements)
3
23
3
Order By: Relevance
“…K. pelamis was identified as the species with the highest Cd bioaccumulation values (p<0.01), with a mean value of 0.035 if compared with T. albacore where a mean value of 0.007 mg/kg was found. From a literature review, the concentrations of Cd we found, have comparable values to that of canned tuna distributed in other national and international markets (52)(53)(54)(55)(56).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…K. pelamis was identified as the species with the highest Cd bioaccumulation values (p<0.01), with a mean value of 0.035 if compared with T. albacore where a mean value of 0.007 mg/kg was found. From a literature review, the concentrations of Cd we found, have comparable values to that of canned tuna distributed in other national and international markets (52)(53)(54)(55)(56).…”
Section: Discussionsupporting
confidence: 65%
“…Regarding to Pb, concentrations found are unexpectedly lower than literature finding related to canned tuna (52,(54)(55)(56)(57)(58). Pollution of Pb is an environmental and public health hazard for its persistence and toxicity.…”
Section: Discussionmentioning
confidence: 56%
“…Tuna fish, like other marine fish species, is very important in the human diet and represents the main source of protein, polyunsaturated fatty acids (PUFAs), vitamins and a wide range of other important nutrients [7,8,9,10,11]. However, large predators, such as albacore tuna, are at the top of the aquatic food chain, and hence they can bioaccumulate large amounts of toxicants, such as the heavy metals mercury (Hg), cadmium (Cd) and lead (Pb) [12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals eating high quantities of tuna may have increased health risks such as developmental anomaly of the brain of infants and neurological problems in adults [22]. Cadmium may induce skeletal weakness, reproductive deficiencies, neurological and digestive disorders, cancers, mutations, and kidney dysfunction [7,23,24,25]. Lead is another known toxicant for human considered as a toxic element due to its biochemical effects which includes hypertension, hematological effects, neurological problems and renal dysfunction [23].…”
Section: Introductionmentioning
confidence: 99%
“…Among aquatic foods, fish are currently consumed, therefore, they are a connecting link for the transfer of toxic heavy metals in human beings [2,3]. Fish are ideal indicators of heavy metals contaminations in aquatic systems [4], because they are constantly exposed to alloys in polluted waters [1,5]and occupied different trophic levels [4]also may accumulate heavy metals, and represent one of the major sources of heavy metals for human [6,7].…”
Section: Introductionmentioning
confidence: 99%